2000
DOI: 10.1093/jn/130.10.2467
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Carnitine Palmitoyltransferase-I Are Altered by Dietary Variables and Suggest a Metabolic Need for Supplemental Carnitine in Young Pigs

Abstract: To examine the kinetics of carnitine palmitoyltransferase-I (CPT-I) and the influence of dietary variables, young pigs (18 kg, n = 20) were fed corn-soybean meal diets supplemented with 40 g soy oil/kg and containing either 136 or 180 g crude protein/kg and either 0 or 500 mg/kg L-carnitine (2 x 2 factorial design). Diets were offered for 10 d (85% of ad libitum); CPT-I activities in liver and skeletal muscle mitochondria were determined, and enzyme kinetic constants (V:(max) and K:(m) for carnitine) were esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 24 publications
4
23
2
Order By: Relevance
“…The ␥-butyrobetaine concentrations measured in human plasma was, however, lower than reported in literature (1.78 M [10]), while the concentration of trimethyllysine was similar (0.88 M [10]). Concentrations of free carnitine and short chain carnitine esters in pig liver and skeletal muscle, presented in Table 3, are similar to those reported by Heo et al [19] who found concentrations of 73.7 and 759.8 nmol/g for free carnitine and of 2.2 and 193.7 nmol/g for short chain acyl carnitines in liver and muscle, respectively.…”
Section: Resultssupporting
confidence: 88%
“…The ␥-butyrobetaine concentrations measured in human plasma was, however, lower than reported in literature (1.78 M [10]), while the concentration of trimethyllysine was similar (0.88 M [10]). Concentrations of free carnitine and short chain carnitine esters in pig liver and skeletal muscle, presented in Table 3, are similar to those reported by Heo et al [19] who found concentrations of 73.7 and 759.8 nmol/g for free carnitine and of 2.2 and 193.7 nmol/g for short chain acyl carnitines in liver and muscle, respectively.…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, dietary carnitine restored the function of liver mitochondria in old rats (Hagen et al 1998). As shown in a recent study, a significant increase in CPT1 activity after 10 days of dietary supplementation with l -carnitine was detected in liver but not in skeletal muscle (Heo et al 2000). Therefore, liver can be considered as a primary target organ for effects of dietary carnitine administration.…”
mentioning
confidence: 77%
“…Moreover, the reduced NEFA concentration in blood plasma indicates that lipid metabolism was influenced during the period of carnitine supplementation. Owing to its essential role for the transportation of long-chain fatty acids into the mitochondrial matrix where b-oxidation of activated fatty acids takes place, carnitine is often associated with increased fatty acid utilization as shown in porcine mitochondria in vitro (Heo et al, 2000) and in liver mitochondria and hepatocytes of carnitine-supplemented growing pigs (Owen et al, 2001). As a result, reduced body fat accretion has been observed in suckling, weaning and growing pigs in response to carnitine (Owen et al, 1996 and2001;Lö sel et al, 2009).…”
Section: Discussionmentioning
confidence: 99%